2D nanocomposite of hexagonal boron nitride nanoflakes and molybdenum disulfide quantum dots applied as the functional layer of all-printed flexible memory device. (September 2018) - Rehman, Muhammad Muqeet; Siddiqui, Ghayas Uddin; ur Rehman, Mohammad Mutee; Kim, Hyun Bum; Doh, Yang Hoi; Choi, Kyung Hyun
Graphical abstract: Highlights: We have proposed a flexible, rewritable and NVM device based on an advanced 2D nanocomposite. 2D nanocomposite is synthesized by mixing hBN flakes and MoS2 QDs. Entire device was fabricated through extremely simple and highly controllable printing technology. The RRAM device was tested electrically, mechanically, thermally and chemically. Abstract: In this study, we have proposed a flexible, rewritable and nonvolatile memory device based on an advanced 2D nanocomposite of hexagonal boron nitride (hBN) flakes and molybdenum disulfide quantum dots (MoS2 QDs). Complete device fabrication was carried out by using extremely simple and highly controllable all printed technology. The electrical characteristics exhibited by the as developed memory devices included the switching ratio, electrical endurance and retention time of ∼10 3, 10 3 and 10 4 respectively. The device turned ON and OFF at the SET and RESET threshold voltages of +1.4 V and −1 V respectively. The obtained results of electrical and thermal characterizations exhibited that the switching ratio decreases via either increasing temperature (300 K–380 K) or device size (42 μm–100 μm) hence verifying the formation of conductive filament through the functional layer. Moreover, no major degradation in the switching characteristics was observed even after 1500 bending cycles.